(untitled) (Proceedings of Southern Federal University. Philology, 2020)
In the conceptual apparatus of methodology spelling is a mixture of concepts of «orthogramm» and «spelling action», due to the methodological aspects of modern methods of spelling, on the one hand, influenced by the linguistic theory of V.F. Ivanova and methodological concept of M.M. Razumovsky, and on the other – under the influence of modern concepts that interpret the theory of speech activity. The article analyzes the problem, proves the feasibility of using spelling action as the dominant concept of the theory and practice of spelling techniques. Spelling action is presented in the light of writing as a type of speech activity, is defined as speech action, cognitive-communicative action, text-forming action. The analysis of the problem of spelling literacy of students from the standpoint of the theory of speech activity, writing as a type of speech activity gives good reasons to actualize in the teaching methodology not orthogram but spelling action. Key words: orthogram, spelling action, written speech, speech action, cognitive-communicative action, text-forming action, methodology, spelling technique. DOI 10.18522/1995-0640-2020-1-190-197